2018
DOI: 10.1088/1361-6404/aad763
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigations of the rolling of a ball on a rotating plane (turntable)

Abstract: In this work we investigate the motion of a homogeneous ball rolling without slipping on uniformly rotating horizontal and inclined planes under the action of a constant external force supplemented with the moment of rolling friction, which depends linearly on the angular velocity of the ball. We systematise well-known results and supplement them with the stability analysis of partial solutions of the system. We also perform an experimental investigation whose results support the adequacy of the rolling fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…The theoretical results obtained supplement the models of motion of a ball without slipping on a rotating plane [2]. The problem under consideration is of great importance for applications.…”
Section: T B Ivanovasupporting
confidence: 52%
See 2 more Smart Citations
“…The theoretical results obtained supplement the models of motion of a ball without slipping on a rotating plane [2]. The problem under consideration is of great importance for applications.…”
Section: T B Ivanovasupporting
confidence: 52%
“…The motion described above is similar to that of the ball on the plane if one incorporates the moment of resistance to rolling which is proportional to the angular velocity of the ball [2]. But in this case the untwisting of the spiral occurs much faster (see also [11]).…”
Section: Explicit Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another open problem is to examine the rolling of the ball with rolling resistance. In the recent paper [1], in the case of motion of a homogeneous ball on a plane, a good agreement was shown between the experimental trajectory and the theoretical trajectory obtained by adding the moment of rolling friction which is proportional to the angular velocity of the ball. Using this friction model, it was shown that all trajectories asymptotically tend to an untwisting spiral.…”
Section: Resultsmentioning
confidence: 62%
“…Заметим, что эти выводы сделаны для сильно деформируемых материалов (например, резины). При анализе экспериментов по трению качения стальных шариков в [12,13] показано, что коэффициент трения пропорционален угловой скорости. Для неоднородного шара (Чаплыгина) в [14] показано, что учёт только трения скольжения (сухого или вязкого) не даёт удовлетворительного согласия с экспериментом, более существенное влияние оказывает трение качения.…”
Section: с л у ч а й н е п р е р ы в н о г о к о н т а к т аunclassified